Optimizing the Role of Bhabinkamtibmas as an Extension of the Intelligence Function in the Prevention and Eradication of Terrorism - Andi Amir Wahyudi; I Made Suwandi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Terrorism is a complex problem that requires serious handling from the security forces. In relation to this statement, lately acts of terrorism have become more and more common because they are caused by the subtle notions that develop in the midst of society so that they are not detected by the security forces, in this case members of the Police. In order to anticipate acts of terrorism as early as possible, the Indonesian National Police actually has officers who can be empowered, namely Bhayangkara for Community Security and Order or Bhabinkamtibmas. This Bhabinkamtibmas officer can maximize his function in preventing and eradicating terrorism. Therefore, in this study, the process of appointing Bhabinkamtibmas officers and also maximizing their role in the prevention and eradication of terrorism will be analyzed further in order to provide an overview of alternatives for preventing and eradicating terrorism in the community.